Valuing Global Public Goods : A European Delphi Stated Preference Survey of Population Willingness to Pay for Amazon Rainforest Preservation - Navrud, Ståle; Strand, Jon (World Bank, Washington, DC, 2014)
The Amazon Rainforest is a global public good. As such, and given that 15 percent of the original Amazon forest area has already been lost, households worldwide might be willing to pay to reduce or avoid additional losses. A full elicitation of global preferences for valuing preservation of the current forest, using stated-preference population surveys, would be costly and time consuming. Alternatively, this paper uses a Delphi stated-preference technique in which 48 European environmental valuation experts were asked to provide "best guesses" on the possible outcomes of population surveys in their own countries and Europe as a whole. The expert judgments indicate willingness to pay in Europe for preserving the current Amazon Rainforest of about 28 Euro per household per year on average; a slightly lower value is inferred for a plan that allows a 10 percent future reduction from the current rainforest area. The income elasticity of experts' stated willingness to pay with respect to per-capita income in their own countries is in the range 0.5-0.8. These findings indicate that Delphi studies might be used more widely as a tool for global benefit transfer.